2021
DOI: 10.1523/eneuro.0055-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Brain Injury Broadly Affects GABAergic Signaling in Dentate Gyrus Granule Cells

Abstract: Traumatic brain injury (TBI) causes cellular and molecular alterations that contribute to neuropsychiatric disease and epilepsy. GABAergic dysfunction figures prominently in the pathophysiology of TBI, yet the effects of TBI on tonic inhibition in hippocampus remain uncertain. We used a mouse model of severe TBI (controlled cortical impact, CCI) to investigate GABAergic signaling in dentate gyrus granule cells (DGGCs). Basal tonic GABA currents were not affected by CCI. However, tonic currents induced by the δ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
29
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(39 citation statements)
references
References 77 publications
(137 reference statements)
6
29
4
Order By: Relevance
“…Tonic and synaptic GABA currents are known to be altered after brain injury with outcomes varying between experimental models. GC tonic GABA current amplitude was reported to be similar to controls 2-20 weeks after murine CCI or severe concussion in adult rats (Pavlov et al, 2011; Boychuk et al, 2016; Parga Becerra et al, 2021) which contrasts with the increase we had reported one week after moderate concussion in adolescent rats (Gupta et al, 2012). Our current demonstration that GC tonic GABA current amplitude remains elevated one month after injury differs from Pavlov et al (2011) and parallels our observation at one week (Gupta et al, 2012), while the recover to control levels by three months is consistent with Pavlov et al (2011).…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Tonic and synaptic GABA currents are known to be altered after brain injury with outcomes varying between experimental models. GC tonic GABA current amplitude was reported to be similar to controls 2-20 weeks after murine CCI or severe concussion in adult rats (Pavlov et al, 2011; Boychuk et al, 2016; Parga Becerra et al, 2021) which contrasts with the increase we had reported one week after moderate concussion in adolescent rats (Gupta et al, 2012). Our current demonstration that GC tonic GABA current amplitude remains elevated one month after injury differs from Pavlov et al (2011) and parallels our observation at one week (Gupta et al, 2012), while the recover to control levels by three months is consistent with Pavlov et al (2011).…”
Section: Discussioncontrasting
confidence: 99%
“…Tonic GABA currents mediated by extrasynaptic receptors contribute to reduced GC excitability (Stell et al, 2003; Brickley and Mody, 2012). Granule cell tonic GABA currents are altered in experimental brain injury (Gupta et al, 2012; Boychuk et al, 2016; Parga Becerra et al, 2021). We previously reported a potentially beneficial increase in GC tonic GABA currents one week after moderate FPI 25-26 day old rats (Gupta et al, 2012), a period that parallels human adolescence in terms of neurological developmental (Semple et al, 2013; Sengupta, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations